Invasive Streptococcus pneumoniae in Canada, 2011–2014: Characterization of new candidate 15-valent pneumococcal conjugate vaccine serotypes 22F and 33F. Issue 23 (17th May 2016) - Golden, Alyssa R.; Adam, Heather J.; Zhanel, George G.; ,
Abstract: Emerging non-PCV-13 Streptococcus pneumoniae serotypes 22F and 33F are included in a new 15-valent pneumococcal conjugate vaccine currently undergoing clinical trials in the United States. This study assessed the antimicrobial resistance and genetic relatedness of these two emerging pneumococcal serotypes. Of the 5075 invasive pneumococcal isolates collected in Canada from 2011 to 2014, 9.8% (497/5075) were serotype 22F and 3.2% (160/5075) were serotype 33F. Despite being among the top 4 most common serotypes collected each study year, serotype 22F demonstrated ≥98% susceptibility to all antimicrobials tested except clarithromycin and few were multi-drug resistant (MDR) (0.8%, 4/497). Serotype 22F isolates were highly clonal (ST433), with two isolates showing high relatedness to MDR international clone Sweden 15A -25 (ST63). Conversely, serotype 33F showed greater antimicrobial resistance, greater genetic diversity and a higher proportion of MDR isolates (8.8%, 14/160). The prevalence of serotype 33F increased significantly during 2011–2014 ( p = 0.005).